the The Effect Of Podcast Based Audio-Visual Learning Media On Students Learning Interest In Indonesian History Sumbject In Grade XI Of SMA Negeri 7 Kota Serang: Pengaruh Media Pembelajaran Audio Visual Berbasis Podcast Terhadap Minat Belajar Siswa Pada Mata Pelajaran Sejarah Indonesia Kelas XI SMA Negeri 7 Kota Serang - Eko Ribawati; Arif Permana Putra3b; khansa hasna sahl (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study aims to determine the effect of the application of podcast-based audio-visual learning media on the learning interest of class XI students of SMA Negeri 7 Kota Serang. This type of research is quantitative using quantitative descriptive analysis and correlation analysis. The sample in this study was class XI-5 SMA Negeri 7 Kota Serang, totaling 36 students. The data collection technique used was through questionnaires and observations. The questionnaire given to respondents consisted of 20 questions for the independent variable (X) and 20 questions for the variable (Y). By using the calculation of the questionnaire that had been given to 36 students using product moment analysis. Then by paying attention to the magnitude of Rxy, namely (0.446546) which is between (0.40) and (5.99), it can be said that the level of correlation relationship is moderate. The calculation of the significant test can be seen that t (2.910037) is greater than t table at a significance level of 5%, namely (2.03), so the alternative hypothesis (Ha) is accepted and the null value (H0) is rejected. This means there is a significant positive influence between variables X and Y. Based on the research results above, it can be concluded that the use of podcast- based audio-visual learning media has an effect on the interest in learning Indonesian History in class XI of SMA Negeri 7 Kota Serang. Therefore, it can be said that podcast media can be recommended as a learning medium used in history learning because this audio-visual–based podcast is able to present material in an engaging way, both in terms of visuals and the accompanying text background. It is easy to understand because the delivery uses simple language, and it is flexible to be played anywhere and at any time.